Autoimmune Diseases in Patients with Cushing’s Syndrome after Resolution of Hypercortisolism: Case Reports and Literature Review - Luigi Petramala; Federica Olmati; Maria Gabriella Conforti; Antonio Concistré; Valeria Bisogni; Nikita Alfieri; Gino Iannucci; Giorgio de Toma; Claudio Letizia (International Journal of Endocrinology)
Introduction. Cushing’s syndrome (CS) is a clinical condition characterized by excessive cortisol production, associated with metabolic complications, such as diabetes mellitus, dyslipidemia, metabolic syndrome, hypertension, and cardiovascular diseases. Nowadays, the occurrence of autoimmune diseases in CS have not been completely evaluated in the previous studies. Objective. The aim of this study was to evaluate the occurrence of autoimmune diseases in CS patients after successfully treated. Materials and Methods. From January 2001 to December 2017, in our Secondary Hypertension Unit, we evaluated 147 CS patients (91 with ACTH-independent disease, 54 with ACTH-dependent disease, and 2 patients with ectopic ACTH production. Results. 109 CS patients (74.1%) were surgically treated (67 ACTH-independent CS patients (61.5%) undergone adrenalectomy and 42 ACTH-dependent CS (38.5%) undergone transsphenoidal surgery) and evaluated after 6, 12, and 24 months after clinical and biochemical remission of disease. In 9 (8.3%) of overall treated CS patients (8.3%), during follow-up, we observed the onset of some manifestations of autoimmune diseases. In particular, one patient had a systemic lupus erythematosus, one patient had rheumatoid arthritis, 4 patients reported autoimmune thyroiditis (Basedow-Graves’ disease and Hashimoto’s thyroiditis), one patient had clinical features of psoriasis, one patient showed myasthenia gravis, and one patient had giant cell arteritis. Conclusions. Our results demonstrate that patients successfully treated for CS could develop autoimmune diseases. Therefore, after treatment, CS patients need to be strictly monitored in order to evaluate the possible onset of autoimmune diseases.